Emerging Trends and Influential Factors in the 2022 Punjab State Elections: A Comparative Analysis of Strategies, Voter Preferences, and Electoral Outcomes - Kanwal Kumar (Journal of Government and Political Issues, 2022)
This study explores the emerging trends and factors that influenced the Punjab Legislative Assembly Elections in 2022, shedding light on the evolving dynamics of electoral politics in India. The research employs a comparative analytical approach, utilizing data from various sources such as published literature, online resources, and databases to examine voter preferences, party strategies, and electoral outcomes. The 2022 elections witnessed an unprecedented victory for the Aam Aadmi Party (AAP), highlighting the shift in voter priorities towards development, unemployment, health, and sanitation. Key findings include the growing importance of social media and digital campaigns in shaping voter preferences, the increasing significance of women and youth voters in the electoral landscape, and the decline of traditional political forces. These results have crucial implications for the future of Indian politics, emphasizing the need for political parties to address changing voter priorities, engage with digital platforms, and cater to the concerns of women and youth demographics. This study provides valuable insights for political parties seeking to navigate the shifting landscape of the world's largest democracy.